The effects of brand equity, price, and brand proliferation on new product performance through product trial: evidence from FMCG industry in Indonesia - Winson Sinurat; I Made Bayu Dirgantara (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2021)
Business competition in fast-moving consumer goods (FMCG) products in Indonesia has increased due to industry growth in this sector. Companies must create new marketing strategies to maintain and gather a broader market share. The purpose of this study is to analyze the effects of brand equity, price, and brand proliferation on new product performance of FMCG products through product trial. This study uses quantitative analysis, which uses data analysis tools SPSS 26) to analyze the data with PROCESS macro analysis to analyze the mediator variables. This study showed that brand equity, product quality, and brand proliferation had a positive and significant effect on new product performance. The PROCESS analysis results also show mediating effects between brand equity, price, and brand proliferation on new product performance through product trial. These results also show that brand equity, price, and brand proliferation can predict new product performance in the FMCG industry in Indonesia.